(untitled) (International Journal of Engineering and Computer Science, 2014)
waterbed and sea floor. Images and Videos are important source of information and aids for their study. However, there are unique set of constraints in underwater environment that have limited our ability to process underwater images. Some of the important constraints in underwater images are associated with the physics of the light and attenuation of the electromagnetic spectrum. Processing issues also need to be dealt for the required application. Some of the research issues underwater have been the tasks associated with reconstructing three-dimensional information about the world from its two-dimensional Projections. In this paper the techniques of underwater video processing for detecting and tracking moving objects are discussed, analysed and compared.